2019
DOI: 10.1371/journal.pone.0210441
|View full text |Cite
|
Sign up to set email alerts
|

A method for the detection and characterization of technology fronts: Analysis of the dynamics of technological change in 3D printing technology

Abstract: This paper presents a method for the identification of the “technology fronts”—core technological solutions—underlying a certain broad technology, and the characterization of their change dynamics. We propose an approach based on the Latent Dirichlet Allocation (LDA) model combined with patent data analysis and text mining techniques for the identification and dynamic characterization of the main fronts where actual technological solutions are put into practice. 3D printing technology has been selected to put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Our preliminary cost analysis has shown that SLS printing of meatal dilators could be an efficient alternative to machining. Although the cost of USD 175,000 for the SLS printer used in this study may present a cost barrier for many institutions, with the expiry of patents the cost of SLS printers continues to decrease over time [31]. Any discussion around cost is likely to change in the future as 3D printing technology continues to evolve and become cheaper and more accessible.…”
Section: Discussionmentioning
confidence: 96%
“…Our preliminary cost analysis has shown that SLS printing of meatal dilators could be an efficient alternative to machining. Although the cost of USD 175,000 for the SLS printer used in this study may present a cost barrier for many institutions, with the expiry of patents the cost of SLS printers continues to decrease over time [31]. Any discussion around cost is likely to change in the future as 3D printing technology continues to evolve and become cheaper and more accessible.…”
Section: Discussionmentioning
confidence: 96%
“…This section highlights the phases and crystal features of 3D-printed HEA products. DED, [144] (b) SLM, [145] and (c) EBM. [146] Reproduced with permission.…”
Section: D Printing Of Heasmentioning
confidence: 99%
“…Reproduced with permission. [145] Copyright 2019, Public Library of Science. Reproduced with permission.…”
Section: D Printing Of Heasmentioning
confidence: 99%
See 2 more Smart Citations